Specialist pneumonia intervention nurse service improves pneumonia care and outcome. Issue 1 (4th August 2021) - Free, Robert C; Richardson, Matthew; Pillay, Camilla; Hawkes, Kayleigh; Skeemer, Julie; Broughton, Rebecca; Haldar, Pranabashis; Woltmann, Gerrit
Abstract : Background: A specialist pneumonia intervention nursing (SPIN) service was set up across a single National Health Service Trust in an effort to improve clinical outcomes. A quality improvement evaluation was performed to assess the outcomes associated with implementing the service before (2011–2013) and after (2014–2016) service implementation. Results: The SPIN service reviewed 38% of community-acquired pneumonia (CAP) admissions in 2014–2016. 82% of these admissions received antibiotic treatment in <4 hours (68.5% in the national audit). Compared with the pre-SPIN period, there was a significant reduction in both 30-day (OR=0.77 (0.70–0.85), p<0.0001) and in-hospital (OR=0.66 (0.60–0.73), p<0.0001) mortality after service implementation, with a review by the service showing the largest independent 30-day mortality benefit (HR=0.60 (0.53–0.67), p<0.0001). There was no change in length of stay (median 6 days). Conclusion: Implementation of a SPIN service improved adherence to BTS guidelines and achieved significant reductions in CAP-associated mortality. This enhanced model of care is low cost, highly effective and readily adoptable in secondary care.